Histological Findings After Aortic Cross-Clamping in Preclinical Animal Models. Issue 10 (17th September 2021) - Awad, Hamdy; Efanov, Alexander; Rajan, Jayanth; Denney, Andrew; Gigax, Bradley; Kobalka, Peter; Kelani, Hesham; Basso, D Michele; Bozinovski, John; Tili, Esmerina
Abstract: Spinal cord ischemic injury and paralysis are devastating complications after open surgical repair of thoracoabdominal aortic aneurysms. Preclinical models have been developed to simulate the clinical paradigm to better understand the neuropathophysiology and develop therapeutic treatment. Neuropathological findings in the preclinical models have not been comprehensively examined before. This systematic review studies the past 40 years of the histological findings after open surgical repair in preclinical models. Our main finding is that damage is predominantly in the grey matter of the spinal cord, although white matter damage in the spinal cord is also reported. Future research needs to examine the neuropathological findings in preclinical models after endovascular repair, a newer type of surgical repair used to treat aortic aneurysms.